UMPSA collaborates with industry to explore Smart Agriculture Innovation - Naqiah, Puaad (UMPSA, 2024)
KUALA LUMPUR, 18 December 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and DSR Fruits Sdn. Bhd. have established a strategic partnership as another significant step in advancing the fields of academia and research.